The effect of ultraviolet diode radiation on the growth rate of Alternaria colonies - Rusakovich, Alina A.; Shashko, Antonina Yu.; Viatoshkin, Aliaksei A.; Saldatsenka , Aliaksei A.; Balvanovich, Uladzimir V.; Smolich, Ihar I.; Sokolik , Anatoliy I.; Shashko , Yuri K.; Demidchik , Vadim V. (Experimental Biology and Biotechnology, 2021)
Phytopathogenic micromycetes induce dangerous crop diseases. Traditionally, fungicides have been used to prevent these diseases. In recent years, environmentally friendly non-chemical methods for combating fungal infections have been developed. In particular, ultraviolet (UV) treatment of various wavelengths, intensities and origins has been shown to be effective. In this work, we have analysed the effect of diode low-intensity shortwave UV radiation (UV-C) on the growth and potential viability of the mycelium of Alternaria radicina and A. alternata, the pathogens of important crops. It was shown that irradiation by UV-C diode inhibited growth of Alternaria species at the early stages of development. This effect was high in the first 3 d after UV exposure; however, after 5 d after irradiation, the growth of pathogenic fungi fully restored, suggesting that UV can be only used for partial removal of Alternaria. It was found that A. alternata is less sensitive to diode UV irradiation. The obtained results indicate that the Alternaria micromycetes, particularly, A. alternata, containing high melanin levels, are resistant to low-intensity UV-C diode irradiation.